2018
DOI: 10.1186/s12871-017-0464-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single-dose dexmedetomidine on postoperative recovery after ambulatory ureteroscopy and ureteric stenting: a double blind randomized controlled study

Abstract: BackgroundAmbulatory surgery has recently gain popularity, as it is a good method of optimizinghospital resources utilization. To support ambulatory surgery, anaesthetic goals nowrevolve around patients’ early recovery with minimal pain and nausea, expedientdischarge home and prompt resumption of activities of daily living. In this study, weevaluated the effect of a single pre-induction dose of dexmedetomidine on anaestheticrequirements, postoperative pain and clinical recovery after ambulatory ureteroscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…Meanwhile, Shariffudin et al found a significant decrease in the systolic blood pressure at the 15-min mark after infusion. This phenomena disappeared by the 20-min mark and did not return for the remainder of the case [69]. It appears that these episodes of hemodynamic disturbance are associated with the use of a loading dose or fast initial infusion rates.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Meanwhile, Shariffudin et al found a significant decrease in the systolic blood pressure at the 15-min mark after infusion. This phenomena disappeared by the 20-min mark and did not return for the remainder of the case [69]. It appears that these episodes of hemodynamic disturbance are associated with the use of a loading dose or fast initial infusion rates.…”
Section: Resultsmentioning
confidence: 91%
“…They reported a reduction of the MAC of sevoflurane (0.6 (0.2) vs. 0.9 (0.1), p = [10,44] 0 . 1 5 -4 mcg/kg 0.2-0.7 mcg/kg/h IV PCA (with opioid) [53,54] 2.5-10 mcg or 0.1 mcg/kg 0.02-0.6 mcg/kg/h basal rate or 2.5-10 mcg/h 10-15-min lockout IV PCA (as sole agent) [9••] 0.25 mcg 0.5 mcg/kg/h 15-min lockout Oral [57] 4 m c g / k g Intranasal [45,58] 1 -2 mcg/kg Buccal [59] 2.5 mcg/kg Intramuscular [59] 2.5 mcg/kg IV, intravenous; PCA, patient-controlled analgesia; min, minute 0.037) needed to achieve adequate sedation, as well as a 60% reduction of pain immediately postop with further reduction lasting until POD 3 [69]. Panchgar et al had similar results in laparoscopic surgeries with a loading dose of 1 μg/kg body weight and then a maintenance dose of 0.5 μg/kg/h for the remainder of the procedure.…”
Section: Clinical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, controversy exists regarding whether preoperative use of alpha-2 agonists as sedatives has an effect on reducing postoperative pain. Shariffuddin et al [ 5 ] concluded that a single dose of dexmedetomidine was a useful adjuvant in reducing postoperative pain, and Sung et al [ 6 ] demonstrated that oral clonidine premedication reduced the requirement of postoperative analgesia in patients undergoing laparoscopic cholecystectomy. However, Lee et al [ 7 ] found that pre-anesthetic administration of a single loading dose of dexmedetomidine given 10 min before induction did not reduce patient-controlled anesthesia consumption of postoperative fentanyl or the pain score.…”
Section: Introductionmentioning
confidence: 99%